2022
DOI: 10.3390/medicina58040514
|View full text |Cite
|
Sign up to set email alerts
|

Eight Weeks of Supervised Pulmonary Rehabilitation Are Effective in Improving Resting Heart Rate and Heart Rate Recovery in Severe COVID-19 Patient Survivors of Mechanical Ventilation

Abstract: Background and Objectives: Patients who survive severe COVID-19 require significant pulmonary rehabilitation. Heart rate (HR) has been used as a safety variable in the evaluation of the results of interventions in patients undergoing pulmonary rehabilitation. The aim of this research was to analyse HR during a pulmonary rehabilitation program in post-severe COVID-19 patients who survived mechanical ventilation (MV). The study includes the initial and final evaluations and aerobic training sessions. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…A higher volume of training >4 months seems beneficial in cardiac [87] as well as in fibromyalgia patients [88,89]. Likewise, the study of Del Valle et al (2022) had shown an improvement of resting HR after 8 weeks of supervised pulmonary rehabilitation on severe COVID-19 survivor patients [90], while we did not find significant improvement for this parameter in our study. The volume and duration of physical activity proposed in this study was certainly too low to expect autonomous changes.…”
Section: Discussioncontrasting
confidence: 45%
“…A higher volume of training >4 months seems beneficial in cardiac [87] as well as in fibromyalgia patients [88,89]. Likewise, the study of Del Valle et al (2022) had shown an improvement of resting HR after 8 weeks of supervised pulmonary rehabilitation on severe COVID-19 survivor patients [90], while we did not find significant improvement for this parameter in our study. The volume and duration of physical activity proposed in this study was certainly too low to expect autonomous changes.…”
Section: Discussioncontrasting
confidence: 45%
“…The study was conducted between September 2020 and March 2021 and was approved by the Scientific Ethics Committee of the Central Metropolitan Health Service, Chile (Resolution N° 378/2021). This study is part of a larger project with previous publications providing preliminary results or secondary analyses [ 14 , 15 ]. All the participants were informed about the procedures of this study, agreed to participate, and signed the informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…to conclude that a PR program could be safe, feasible, and effective in patients post COVID-19 after the acute stage, thereby improving their pulmonary function, strength, and quality of life [18]. Thus, PR has proven to be an intervention model with multisystemic impact, which generates signi cant improvements in the cardiorespiratory and musculoskeletal systems, regardless of the severity of the clinical picture [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted between September 2020 and March 2021 and was approved by the Scienti c Ethics Committee of the Central Metropolitan Health Service, Chile (Resolution N° 378/2021). This study is part of a larger project with previous publications providing preliminary results or secondary analyses [12,13]. All the participants were informed about the procedures of this study, agreed to participate, and signed the informed consent.…”
Section: Participants and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation